Cyclooxygenase-2 expression in lung in patients with congenital heart malformations and pulmonary arterial hypertension - Loukanov, Tsvetomir; Jaschinski, Christoph; Kirilov, Milen; Klimpel, Homa; Karck, Matthias; Gorenflo, Matthias (The thoracic and cardiovascular surgeon, 2013)
Pulmonary arterial hypertension (PAH) is a cause of morbidity in patients with congenital heart disease (CHD). It has been hypothesized that prostanoides participate in the development of PAH. The aim of this study was to show the potential expression of cyclooxygenase-2 (COX-2) in patients with CHD and PAH.